Different Aspect of Transperitoneal Laparoscopic Pyelolithotomy for Management of Pelvic Stones Larger than 20 mm: a Cuasi-Experimental Study in Male Patients - Pakmanesh, Hamid; Mirzaei, Mahboubeh; Mohammad_Salehi, Sohrab; Sharifian, Rayka (Archives of Men's Health, 2020)
Background: We study different aspect of laparoscopic pyelolithotomy (LP) in patients with large renal pelvis stone regarding success rate, complications as well as the recurrence free status. Material and methods: From July 2015 to January 2019, 32 patients underwent LP for single large renal pelvis stone ($\ge$2 cm). Patient characteristics, preoperative and postoperative hemoglobin, creatinine as well as possible complications based on Clavien classification were recorded. Stone free status was evaluated using computed tomography scan one month after the surgery. Any particle bigger than 4 mm was considered as significant residual stone. During the next one years after the operation, renal ultrasonography was performed for all patients every six month to find any stone recurrence. Results: Mean operation time was 134.55$±$31.41 minutes. Patients were hospitalized 3.36$±$1.13 days in the LP group. Patients showed hemoglobin decrease of 1.50$±$1.05 (P=0.2). Stone free rate was 93.75% and Mean overall stone free status estimated to be 32 months. Conclusion: PCNL has been the treatment of choice for large renal pelvis stones; however, in expert hands, LP is an appropriate substitute with superior stone free rate, less bleeding and remarkably less stone recurrence.